2019
DOI: 10.1016/j.cardfail.2019.07.341
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Accident in a Patient with Left Ventricular Assist Device and Therapeutic INR: Should Left Atrial Appendage Be Routinely Closed?

Abstract: discovered with advanced imaging modalities such as computed tomography (CT) of the chest. Conclusion: Calcified apical aneurysms can develop in patients with ICMP and advanced CHF and should always be looked for before LVAD implantation. Advanced imaging techniques, such as CT of the chest, can help to identify such calcified aneurysms preoperatively and safely tailor surgical plans in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This can reduce atrial fibrillation in long-term in some LVAD patients. Despite other improvements in left atrial parameters, preliminary evidence suggests that the left atrial appendage continues to have contractile dysfunction and may be a site of thrombosis despite mechanical unloading and anticoagulation with LVAD implantation [17][18][19][20][21][22][23][24]. Significant valvular disease can also persist in some patients and is associated with higher atrial pressures, atrial dilation, and early hospitalization and death [11,12].…”
Section: Pathophysiology Of Atrial Arrhythmias In Left Ventricular Assist Devices Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can reduce atrial fibrillation in long-term in some LVAD patients. Despite other improvements in left atrial parameters, preliminary evidence suggests that the left atrial appendage continues to have contractile dysfunction and may be a site of thrombosis despite mechanical unloading and anticoagulation with LVAD implantation [17][18][19][20][21][22][23][24]. Significant valvular disease can also persist in some patients and is associated with higher atrial pressures, atrial dilation, and early hospitalization and death [11,12].…”
Section: Pathophysiology Of Atrial Arrhythmias In Left Ventricular Assist Devices Patientsmentioning
confidence: 99%
“…Although initial studies suggested that a history of atrial fibrillation was associated with increased risk of thromboembolism after LVAD, the majority of subsequent studies have demonstrated no increased risk of thromboembolic or bleeding events [2 ■■ ,5,6,7 ■ ,8,9, [17][18][19][20]. Though this data is heterogeneous with variable definitions of atrial fibrillation, differing anticoagulation and antiplatelet practices, and inclusion of different LVAD pump types, in totality it implies that the inherent thrombogenicity of LVAD therapy makes the contribution of atrial fibrillation to thromboembolic risk marginal.…”
Section: Impact Of Atrial Arrhythmias On Clinical Outcomes In Left Ventricular Assist Devices Patientsmentioning
confidence: 99%
See 1 more Smart Citation